The impact of COVID-19 on health workers: A health labor market perspective to improve response - Juana Paola Bustamante Izquierdo; Giorgio Cometto; Khassoum Diallo; Pascal Zurn; Jim Campbell (Global Labor Organization (GLO), 2024)
This paper uses a health labor market lens to examine the impact of COVID-19 on health workers, as well as relevant policy levers. It compiles a collection of literature using a standardized measurement framework to determine the impact of COVID-19 on health workers. It examines the relevant issues under the lens of a health labor market. In particular, the paper interprets this information and knowledge by focusing on the supply, demand, and mismatches in a health labor market. Within this framework, it presents relevant issues on COVID-19 and its impact on health workers, as well as the ensuing policy response. Finally, the chapter presents key lessons learned from COVID-19 to inform future responses related to ensuring a sufficient workforce to tackle them.
Keywords: I11; I14; I18; J08; J21; J23; J49; 330; labour market; employment; health; health workforce; supply; demand